Adapting Skills Training to Address Constraints to Women’s Participation - Beegle, Kathleen; Rubiano-Matulevich, Eliana (World Bank, Washington, DC, 2020)
This Jobs Solutions Note identifies practical solutions for development practitioners to design and implement skills training programs that improve outcomes for women. Based on curated knowledge and evidence for a specific topic and relevant to jobs, the Jobs Solutions Notes are not intended to be exhaustive; they provide key lessons, solutions and approaches synthesized from the experiences of the World Bank Group and partners. This Note draws on rigorous evidence stemming from impact evaluations, systematic reviews, meta-analyses, and mixed-methods. The Note focuses on adaptations to address supply-side constraints, while acknowledging the importance of demand-side factors in influencing returns to skills training and labor market outcomes.